2016
DOI: 10.1038/jhh.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetables consumption and incident hypertension: dose–response meta-analysis of prospective cohort studies

Abstract: The role of dietary factors on chronic diseases seems essential in the potentially adverse or preventive effects. However, no evidence of dose-response meta-analysis of prospective cohort studies has verified the association between the intake of fruit and/or vegetables and the risk of developing hypertension. The PubMed and Embase were searched for prospective cohort studies. A generic inverse-variance method with random effects model was used to calculate the pooled relative risks (RRs) and 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 54 publications
12
54
0
1
Order By: Relevance
“…Third, risk factors were only considered at the time of baseline recruitment and possible changes in risk factor status during the follow-up period were not taken into account. Finally, we did not have access to some potential predictors of hypertension such as genetic susceptibility, air pollution, nutritional status and family history of hypertension [4,6,41] in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, risk factors were only considered at the time of baseline recruitment and possible changes in risk factor status during the follow-up period were not taken into account. Finally, we did not have access to some potential predictors of hypertension such as genetic susceptibility, air pollution, nutritional status and family history of hypertension [4,6,41] in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that intracellular potassium reduction is compensated for by elevated sodium levels and, as a consequence, blood pressure elevation [87]. In this context, studies have showed that a higher intake of fruit, vegetables [88,89,90], and some specific nutrients (i.e., potassium and magnesium) [91,92,93] are associated with a lower hypertension risk. However, there are no studies evaluating the effect of specific dietary interventions correcting low-grade metabolic acidosis on the hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…Persons eating higher levels of VFs may be more likely to take up other healthy lifestyles, such as a lower prevalence of obesity and alcohol use, less physical inactivity and tobacco smoking [45], and a less prevalence of hypertension [46]. However, most included studies have adjusted for a wide range of potential confounders.…”
Section: Discussionmentioning
confidence: 99%